Hubungan antara Organisasi BEM dengan perilaku Pro-Sosial Mahasiswa STIAB Smaratungga - Ipah, Ipah; Mujiyanto, Mujiyanto; Supartono, Supartono (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Membership and active involvement in BEM provides students with the opportunity to grow their leadership talents, supervise teams, and oversee ventures that benefit students and the surrounding campus community. In addition, BEM plays a role in supporting a code of ethics, integrity, and responsibility in its members, thereby shaping student behavior in a way that is achieved. This investigation uses quantitative techniques, using a correlational research design, to ascertain and examine the relationship between the BEM organizational entity and students' prosocial attitudes. at STIAB Smaratungga. The results obtained from data analysis reveal an affirmative correlation between BEM membership and students' prosocial behavior, with the regression equation strengthening this relationship. Therefore, these findings strengthen the idea that involvement in BEM has the capacity to shape students' prosocial behavior at the Smaratungga College of Buddhist Studies (STIAB), which in turn can have a beneficial influence on the campus environment and society in general.